Early Christian spirituality of ‘seeing the divine’ in 1 John - Merwe, Dirk G. van der (HTS Teologiese Studies / Theological Studies, 2015)
Apophatic theology and cataphatic theology both occur in the corpus Johanneum to describe the character of God. Apophatically the Gospel of John and the first epistle of John state that ‘nobody has ever seen God’. Cataphatically, Jesus teaches in the Gospel that, ‘Whoever has seen me has seen the Father’, and in 1 John we read that after the Parousia has taken place ‘we know that when he appears we shall be like him, for we shall see him as he is’. This article focuses on the cataphatic phrase ‘we shall see him as he is’ (1 Jn 3:2). This investigation responds to the variety of interpretations of this particular phrase, as well as to the interest in the spirituality that it could have evoked amongst the readers of this epistle. In order to gain clarity on the ‘spirituality of “seeing him” in the first epistle of John’, this research focuses on the mechanisms used by the elder in the text to create spiritualities in the readers, such as the composition of images in the imagination of these early Christians, the dynamic interactions between the reader and the text, as well as the dialectic of pretension and retention in the reading of a text.
free
Keywords: Apophatic theology; Bible. Epistle of John I; Bible. Epistle of John I – Criticism; Literary; Bible. Epistle of John I – Theology; Dialectic; Epistles-Revelation – Catholic Epistles.; God – Face; God – Knowableness; Image (Theology); Jesus Christ; Kataphatic theology; Open access; Peer reviewed; Spiritual life – Biblical teaching; Vision – Religious aspects